PERANCANGAN TATA LETAK WAREHOUSE BARU UNTUK MENINGKATKAN KAPASITAS PENYIMPANAN MATERIAL DENGAN METODE DEDICATED STORAGE DI PT.XX - Ucok Mulyo Sugeng (Fakultas teknik Universitas Muhammadiyah Jakarta, 2016)
PT.XX is an industrial manufacturing company engaged in the assembly of instrument clusters for motorcycles. Increased production capacity in 2015 PT.XX previously as many as 2500 units / day to 3,000 units / day impact on the increase in the number of materials that are stored in the warehouse. Problems that occur in the warehouse PT.XX is not able to accommodate the material to be produced, so that the placement of the material is done by not according to standard. Therefore it is necessary for the removal of material from the old warehouse to the new warehouse. In designing the layout for the new warehouse authors consider the following points, namely: Standart material storage, warehouse area calculation, the determination of the amount of material, the required number of pallets and pallet layout aims to maximize storage and easy retrieval of material. After relayout, warehouse capacity increased 31.7% from the previous, and storage of materials in accordance with company standards.